The association of motor reserve and clinical progression in Parkinson’s disease - Xueqin Bai; Shiwei Zhang; Qiuyue Li; Tao Guo; Xiaojun Guan; Andan Qian; Shuangli Chen; Ronghui Zhou; Yitong Cheng; Haoxin Chen; Zhaoke Gou; Chenglong Xie; et al. (NeuroImage: Clinical)
Objective: To explore the association of motor reserve (MR) and clinical progression in Parkinson’s disease. Methods: This longitudinal study using data from the Parkinson’s progression markers initiative. Patients with de novo PD who underwent dopamine transporter scans at baseline and finished at least five years clinical follow-up assessments (including motor, cognitive, and non-motor symptoms) were included. The individual MR of PD patients were estimated based on initial motor deficits and striatal dopamine depletion using a residual model. Linear mixed-effects models (LME) were performed to examine the associations of baseline MR and clinical progression. Results: A total of 303 de novo PD patients were included and the mean follow-up time was 8.95 years. Results of LME models revealed that the baseline MR was associated with motor, cognitive, and non-motor symptoms in PD patients. There was a significant interaction between MR and disease duration for longitudinal changes in motor (p < 0.001), cognitive (p = 0.028) and depression symptoms (p = 0.014). PD patients with lower MR had a more rapid progression to postural instability and cognitive impairment compared with those with higher MR (p = 0.002 and p = 0.001, respectively). Conclusions: The baseline MR of PD patients were associated with motor and non-motor symptoms and can predicted disease prognosis, suggesting that the initial MR in PD would be associated with the individual’s capacity to cope with neurodegenerative process as well as comprehensive prognosis.